The Community of Inquiry Perspective on Teachers’ Role and Students’ Evaluations of Online Project-Based Learning - Pengyue Guo; Nadira Saab; Danli Ren; Wilfried Admiraal (Online Learning, 2022)
The role of teachers is an important element of online project-based learning courses. Based on the Community of Inquiry framework, this study examined how students’ perceptions of teaching presence, through social presence and cognitive presence, were related to their evaluations of online project-based learning. A 16-week online project-based legal education course was implemented. During the course, students engaged in two small group activities and created two final products. Survey data were collected twice from 38 and 41 students in two course phases. Results from partial least squares analyses revealed that teaching presence was directly related to students’ evaluations in the early stage of the course and indirectly related to students’ evaluations, through the effects of social presence, in the entire course. Practical implications for teachers and suggestions for further studies are provided.